Kaidah Istifham Menurut Az-Zamakhsyari dan Al-Baidlawi - Muhammad Mutawakkil Alallah K (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
In understanding the Quran, nothing can be ruled out, including the linguistic rules used in the Quran. Because, each rule has its own effect in the Quran, including istifhām. Furthermore, istifham which is usually a question, can have other meanings, such as taqrīr, inkarī, irsyād, nahi, taubīkh, ta’ajjub, amr, ifhām, tamannī, taswiyah, ikhbār, etc. Although linguists try to formulate the function of istifhām, but the product is not the finale guide. On the other hand, mufasirs have their own perspective regarding istifhām and its function. Then, the results of this study, it is known that az-Zamakhsyarī in Al-Kasysyāf ‘an Haqāiqi Gawāmid at-Tanzīl and Al-Baiḍāwī in Anwār at-Tanzīl wa Asrār at-Ta`wīl, have different ways of reading regarding the function of istifhām in certain verses. With this result, it becomes clearer if the function of istifhām are ijtihadī, so that reading on it tends to always vary.